Review on the protective mechanism of astragaloside IV against cardiovascular diseases - Chunkun Yang; Qingquan Pan; Kui Ji; Zhuang Tian; Hongyuan Zhou; Shuanghong Li; Chuanchao Luo; Jun Li (Frontiers Media S.A., 2023)
Cardiovascular disease is a global health problem. Astragaloside IV (AS-IV) is a saponin compound extracted from the roots of the Chinese herb Astragalus. Over the past few decades, AS-IV has been shown to possess various pharmacological properties. It can protect the myocardium through antioxidative stress, anti-inflammatory effects, regulation of calcium homeostasis, improvement of myocardial energy metabolism, anti-apoptosis, anti-cardiomyocyte hypertrophy, anti-myocardial fibrosis, regulation of myocardial autophagy, and improvement of myocardial microcirculation. AS-IV exerts protective effects on blood vessels. For example, it can protect vascular endothelial cells through antioxidative stress and anti-inflammatory pathways, relax blood vessels, stabilize atherosclerotic plaques, and inhibit the proliferation and migration of vascular smooth muscle cells. Thus, the bioavailability of AS-IV is low. Toxicology indicates that AS-IV is safe, but should be used cautiously in pregnant women. In this paper, we review the mechanisms of AS-IV prevention and treatment of cardiovascular diseases in recent years to provide a reference for future research and drug development.